2014
DOI: 10.14202/vetworld.2014.284-290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a specific combination of carvacrol, cinnamaldehyde, and Capsicum oleoresin on the growth performance, carcass quality and gut integrity of broiler chickens

Abstract: Awaad MHH, Elmenawey M and Ahmed KA (2014) Effect of a specific combination of carvacrol, cinnamaldehyde, and on the growth performance, carcass quality and gut integrity of broiler chickens, 7(4): 284-290.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
3
31
1
1
Order By: Relevance
“…Short-and medium-chain fatty acids, as well as essential oils (EO), can be considered promising candidates for preventing NE. EO have been reported to possess in vitro antimicrobial and antioxidant activities against a wide range of pathogenic bacteria [9], as well as to improve intestinal integrity and fortify the mucosal barrier [10], and to enhance cellular and humoral immunity [11]. On the other hand, short-chain fatty acids (SCFAs) are either simple mono-carboxylic acids such as formic, acetic, propionic, and butyric acids or carboxylic acids with the hydroxyl group such as lactic, malic, tartaric, and citric acids or short-chain carboxylic acids containing double bonds like fumaric and sorbic acids [12].…”
Section: Introductionmentioning
confidence: 99%
“…Short-and medium-chain fatty acids, as well as essential oils (EO), can be considered promising candidates for preventing NE. EO have been reported to possess in vitro antimicrobial and antioxidant activities against a wide range of pathogenic bacteria [9], as well as to improve intestinal integrity and fortify the mucosal barrier [10], and to enhance cellular and humoral immunity [11]. On the other hand, short-chain fatty acids (SCFAs) are either simple mono-carboxylic acids such as formic, acetic, propionic, and butyric acids or carboxylic acids with the hydroxyl group such as lactic, malic, tartaric, and citric acids or short-chain carboxylic acids containing double bonds like fumaric and sorbic acids [12].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the results obtained from the study agreed with those of other studies. Awaad et al (2014) reported that a 100 g/ton addition of CAP (2.18%) + CAR (5.04%) + CIN (2.90%) reduced the BWG in comparison to the control in a 1-week period, did not change it in a period of 1-3 weeks, and increased it in a period of 3-5 weeks. Bravo et al (2011) reported that, the CAR (5%) + CIN (3%) + CAP (2%) mixture was not effective by 100 mg/kg combination in 1-22 nd days on BWG, while Karadas et al (2014) found that addition of the same mixture and dosage to the feed increased BWG by 86 g in comparison to the control in the period of 0-21 st days.…”
Section: Growth Performancementioning
confidence: 98%
“…According to Al-Kassie (2009), addition of 200 ppm carvacrol reduced the abdominal fat ratio, while addition of 200 ppm cinnamon oil increased it. Awaad et al (2014) reported that the addition of CAP+CAR+CIN to the feed reduced the abdominal fat by 0.27% in comparison to the control group. Considering Table 9, the difference among the groups in terms of the circulation and secretion organs obtained from the slaughtered animals and the ratios of these in total live weight was not significant (p>0.05).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Fu et al [13] also demonstrated the effectiveness of a Chinese herbal extract made from licorice, luhanguo, chrysthemum, and Chinese tea in the inhibition of the FMD virus in BHK21 cells and suckling mice. The simultaneous administration of PE consisting of carvacrol, cinnamaldehyde, and capsicum oleoresin with the Newcastle disease vaccine enhanced immunoglobulin production in broiler chickens, indicating that PE could partially counter immune dysfunction [31]. In addition, the antiviral activity of PE obtained from turmeric, Ashwangandha, and Tulsi plant against FMDV has been reported; but the mechanism for this was unclear if it was due to the inhibition of phytochemicals for viral attachment, entry, replication assembly, and transmission from one cell to other [18].…”
Section: Phytonutrient Did Not Affect Immune Response Measured After mentioning
confidence: 99%